Implementasi Kurikulum 2013 Ditinjau dari Jadwal dan Alokasi Waktu Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan Sekolah Menengah Pertama Kota Banjar Baru - Abd. Hamid, Halisa Normawarni; Irianto, Tri (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2021)
This study aims to 1. find out whether the time allocation is right or not to be taken and applied at school 2. know whether the schedule is right or not to be taken and applied at school. The sample or subjects studied in this study were the Banjarbaru City Education Office and the State Junior High School institutions in partnership with LambungMangkurat University, Banjarbaru City, which amounted to 3 schools. Collecting data in this study in the form of interviews, questionnaires, documentation, semester programs and annual programs from the State Junior High School Curriculum Section, principals and teachers of Physical Education, Sports and Health class VII. In this study the data obtained that the schedule of physical education, sports and health subjects in junior high school in class VII is 1 meeting per week, and in the time allocation of physical education, sports and health in 3 junior high schools in Banjarbaru City that partner with LambungMangkurat University for grade VII, which is 2 schools applying 3 hours of weekly lessons and 1 hour of duration of 45 minutes, while there is 1 school with an allocation of 3 hours of weekly lessons and 1 hour of duration of 40 minutes.